Is Modified Retroperitoneal Lymph Node Dissection Alive for Clinical Stage I Non-Seminomatous Germ Cell Testicular Tumor? - Basiri, Abbas; Ghaed, Mohammad Ali; Simforoosh, Nasser; Tabibi, Ali; Danesh, Abdolkarim; Nouralizadeh, Akbar; Kardoust Parizi, Mehdi (Urology Journal, 2013)